Emotional and social loneliness as mediators of chronic conditions and depression in older adults in Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Distance, New Zealand - Nicholson, Thomas (Massey University, 2024)
Background and Objectives: Aotearoa New Zealand is experiencing an acceleration in its ageing population that will present economic and health challenges for its people and healthcare systems. Modern changes in healthcare enable people to live longer but have come with increased chronic conditions. Adding to this burden, older adults are vulnerable to psychological problems such as depression, itself often considered a chronic condition. Searching for ways to understand and prevent depression in older adults, researchers discovered connections with both chronic conditions and loneliness. The relationship between chronic conditions, loneliness, and depression is complex and not well understood. While considerable research suggests that these components are related, a dearth of research addresses all three components concurrently. Given that chronic conditions are potential risk factors for both depression and loneliness and that loneliness may predict depression, it is conceivable that loneliness may mediate the relationship between chronic conditions and depression. Consequently, it may be possible to prevent or alleviate depression in older adults experiencing chronic conditions by addressing loneliness. Method: Analyses used survey data from 3,011 participants aged 55-91 years taken from two waves of the New Zealand Health, Work and Retirement Study. Two structural equation models tested the relationship between chronic conditions and depression, between multimorbidity and depression, and whether emotional or social loneliness mediated the relationships. Covariates included age, ethnicity, gender, partner status, and SES measured as living standards. Results: SEM analyses found that sleep disorder and multimorbidity predicted depression and that sleep disorder predicted social and emotional loneliness while multimorbidity predicted emotional loneliness. Additionally, SES predicted depression and both types of loneliness. However, loneliness did not mediate either relationship. Conclusion: The current study supports prior research findings that sleep disorder and multimorbidity predict depression. This study further provides a valuable contribution to the literature investigating the relationship between SES when measured as living standards and depression in older people and aligns with the considerable research on the importance of inequalities and their negative impact on health outcomes.
Keywords: chronic conditions; depression; living standards; lonliness; older adults; 520106 Psychology of ageing